IDENTIFIKASI SENYAWA TOKSIK EKSTRAK KLOROFORM KULIT BIJI NYAMPLUNG (Calophyllum inophyllum L.) - Rahayu Santi, Sri; Suirta, I Wayan; Agus Andika Pratama, Kadek (Jurnal Kimia (Journal of Chemistry); Vol. 6, No. 2 Juli 2012)
Identification  of active toxic compounds from chloroform extract Nyamplung skin bean ( Calophyllum inophyllum L) have been conducted. As much as 2,85 g n -hexane extract, 7,42 chloroform extract, and 4,71 water extract were resulted from 1 kg Nyamplung skin bean. Separation of  2 g  chloroform extract  using column chromatography (stationary phase: silica gel 60 and mobile phase chloroform-methanol 9,5:0,5) resulted  in four fraction with yellowish fraction (0,473 g) as the most toxic fraction (LC 50 8,241 ppm). Identification using GC-MS showed that the isolate was hexadecanoic acid (21,02%), 8-octadecenoic acid (59,55%), and oktadecanoic acid(19,43%).
Keywords: Calophyllum inophyllum L., Nyamplung, toxicity